Certain Important Aspects of Legal Norms Defining Essence of Disciplinary Misconduct in Public Service - Kasradze, Iza (Journal of Law, 2019)
The integration process of Georgia with EU and sustainable democratic development of the country has necessitated the reformation of public service legislation. The Law on Public Service of October 31st, 1997 valid untill July 1st, 2017, left many significant elements of public service beyond the regulatory scope. The result was a very vague and ambiguous practice of enforcement with regards to issues which need a unified approach.[1] Taking this into account, in the context of public administration reform, the Parliament of Georgia passed a Law of Georgia on “Public Service” on October 27th, 2015, as a far more refined legislative act geared towards a professional public servant. The new Law introduced numerous novel and innovative institutions for Georgia as well as envisioned norms set to improve the already existing ones. One of such issues was the disciplinary liability of the public servant. Chapter 10, containing provisions regulating disciplinary liability of public servant and stipulating more complete rules of disciplinary liability appeared in the new law, also envisaging disciplinary proceedings. Likewise, disciplinary misconduct was given a new definition, which, in some ways, is different from the previous one. Thereby, the aim of this article is to discuss and analyze new legal norms defining the essence of disciplinary misconduct in public service and to represent their important aspects as they create certain foundation for the effective functioning of the public service sector. * Ph.D. Student at Iv. Javakhishvili Tbilisi State University, Faculty of Law [1] Explanatory Note to Law of Georgia on Public Service, of October 27th, 2015 (Registration № 07-2/372/8), 1, <http://bit.ly/2t7maWS>, [26.03.2019].